Analysis of the Role of Funding Sources in Supporting the Sustainability of Angkringan MSME Businesses - Sarumaha, Risnawati; Maryani, Tri (Mahesa Research Center, 2025)
This study aims to analyze the role of funding sources in supporting the sustainability of angkringan MSME businesses in Bawen, Semarang Regency. Using a qualitative approach with a descriptive research type, this study focuses on the access to funding received by angkringan MSMEs as well as the challenges and impacts on business development. The subjects of the study consisted of four Angkringan MSME owners who actively received funding and one representative from a financial institution providing micro-business credit. Data were collected through in-depth interviews, field observations, and document analysis related to funding policies. The results of the study indicate that funding, especially from Micro Business Credit (KUM), plays a significant role in increasing business capacity, product quality, and infrastructure development. As many as 80% of respondents reported an increase in turnover and competitiveness after receiving funding. However, there are still obstacles in the complex application procedures and limited loan flexibility. Therefore, closer collaboration is needed between financial institutions and business actors to create a more accessible and sustainable funding scheme.